Pengaruh Penempatan Karyawan dan Pengembangan Karir Terhadap Kinerja Karyawan - Tio Christin Andini Naibaho; Injelly tangka; Mutiara Amin; Glorya Kumakauw; Lavenia Mukuan; Jelsen Kaawoan; Marchel Watania; Joubert Maramis (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Abstract: This study aims to examine the effect of: (1) Employee placement and career development on employee performance, (2) Employee Placement on career development This study aims to examine the effect of: (1) employee placement and career development This study uses a qualitative focus interview design. The population in this study are employees at PT. Mandala Finance Manado, totaling 31 employees. Data were collected through questionnaires and then analyzed using multiple linear regression analysis techniques. The results showed that: (1) employee placement has a positive and significant effect on career development, (2) career development has a positive and significant effect on employee performance. (3) employee placement and career development have a significant effect on employee performance. Keywords: employee placement, career development, employee performance